Public give positive feedback - Lee, Pei May; Aminudin, Rabi'ah; Abdul Hamid, Rohana; Shukri, Syaza Farhana Mohamad; Jamaiudin, Norhaslinda (2020)
At this time of writing, the number of confirmed cases worldwide was 22.4 million, and the United States topped the list with over five million cases.